(3EOGQI GdehGQO GdHTQjIs - (3eLjO(B, (3GdcQNjs ((3YeGf(B:s (3OGQ GdefGgL ddfTQ hGdJhRjY(B,s, 2013)
(3eOGNd Gdi GdehGQO GdHTQjI, ESJQGJjLjI GdehGQO GdHTQjI, JMdjd hJhUja hJUeje GdhXGFa, JMOjO GdGMJjGLGJ ef GdehGQO GdHTQjI, GSJbWGH GdehGQO GdHTQjI hJbjje COGA GdYGedjf, GdJOQjH hGdJfejI GdEOGQjI, Jbjje GdhXGFa hgjcd GdCLhQ hGdQhGJH, GdMhGaR hGdeRGjG , GdeSGQ GdhXjaj, EOGQI GdMQcI GdhXjajI, CfXeI GdCef hGdSdGeI GdegfjI, GfVHGW GdehXajfs
Keywords: (3EOGQI (B-(3GdehGQO GdHTQjIs; (3EOGQI GdCaQGOs; (3Gdbhi GdYGedIs